Incentives, Performance and Choking in Darts - Bouke Klein Teeselink; Rogier J. D. Potter van Loon; Martijn J. van den Assem; Dennie van Dolder (Tinbergen Institute, 2018)
This paper examines the effect of incentives on the performance of darts players. We analyze four data sets comprising a total of 123,402 darts matches of professional, amateur, and youth players. The game of darts offers an attractive natural research setting, because performance can be observed at the individual level and without the obscuring effects of risk considerations and the behavior of others. We find that amateur and youth players perform better under moderately higher incentives, but choke when the incentives are really high. Professional players similarly display better performance under higher incentives, but appear less susceptible of choking. These results speak to a growing literature on the limits of increasing incentives as a recipe for better performance.
Keywords: D01; D91; Z20; 330; incentives; choking under pressure; performance; darts